Trial application of acceptance and commitment therapy principles to reduce the degree of stress experienced by adolescents with down syndrome sibling(s) - Afada Alhaque; Poeti Joefiani; Esti Wungu (Psychological Research and Intervention, 2019)
This study was conducted to see whether the training module of the application of the principle of Acceptance and Commitment Therapy can be used as an intervention to reduce the stress degree of adolescents aged 14 – 16 who have Down Syndrome’s sibling. The design of this research is quasi-experiment with One Group Pretest - Posttest Design method. The sample of the study were three adolescents aged 14 – 16 who had Down Syndrome’s sibling, were obtained by purposive sampling technique. The measuring tool used in this study is the Stress Degrees questionnaire, based on stress theory by Lazarus and Folkman (1984), to measure the stress degree, and the Acceptance and Action Questionnaire II (AAQ-II) questionnaire to measure psychological flexibility, adapted into Indonesian from AAQ-II (Hayes, et al, 2004). The results showed that the application of the ACT principle significantly reduced the stress degree and increased the psychological flexibility of adolescents aged 14 – 16 who have Down Syndrome’s sibling, with a significance value of 0.016 (sig 0.05). Through the application of ACT principles, the subjects's psychological flexibility is increased so that the subjects know how to deal with problems, by accepting negative or unpleasant feelings and thoughts because of having Down Syndrome’s sibling and having a commitment to achieve goals according with their value of life.